#### Answer

Fe2O3 + 3CO --> 2Fe + 3CO2

#### Work Step by Step

Fe2O3 + CO --> Fe + CO2
First we balance the Fe since it appears only once on each side. There are 2 on the left and only one on the right so we multiply the right by 2
Fe2O3 + CO --> 2Fe +CO2
Next we balance the Cs and we have 1 on the left and 1 on the right.
Next we balance the Os and we have 4 on the left and 2 on the right so we need to multiply the CO2 by 2 on the right.
Fe2O3 + CO --> 2Fe + 2CO2
Now the Os are balanced but the Cs are not. We multiply the CO by 2
Fe2O3 + 2CO --> 2Fe +2CO2
Now we have 5 Os on the left and only 4 on the right so we add one to the left to get an even number by adding another CO.
Fe2O3 + 3CO --> 2Fe + 2CO2
Now we need another C on the right
Fe2O3 + 3CO --> 2Fe + 3CO2
Now the Os are balanced with 6 on the left and 6 on the right